Islamic Religion and Terrorism in Nigeria: A Critical Review - Stella Eme Osim (HUMAN: South Asian Journal of Social Studies, 2021)
Globally, there are various actors staging violence against civilians to foster fear and suspicion of others. People in many countries are convinced that terrorism represents the most significant threat to their daily lives. There are political movements that take advantage of tragedy and stage citizens against each other to gain greater support. It is important to remember that terrorism is not a new phenomenon. Many countries have suffered for decades from groups, both internal and external including both State and non-State actors, wielding violence against civilians as a political strategy. In many cases, the local population emerged stronger and more resilient, proving that brutality is no match in the long term for the progress of unity and shared values. Religion on the other hand is intended to mold character for a violent free world. Islam has been getting an extremely bad reputation across the world and Muslims have had to face some major hate because of it. People feel it is okay to blame the religion and its teachings and mar Islam's reputation. Hence, this paper studies the nexus between Islamic religion and terrorism in Nigeria and elucidates the impact of the Islamic religion on terrorism in relation to having a violence-free Nigeria. The scope of this paper however is a reconnoiter of the extent to which Islamic religion has been a causative factor or a panacea to terrorism in Nigeria and finds that Islam is a religion of peace but the Quran- which is the Islamic Sacred Book and rule of faith, has suffered major misunderstanding in the hands of ignorant extremists and fanatics distorting this view. This study adopts an evaluative method of research to arrive at its findings